Analysis of the environmental legislation of the Republic of Kazakhstan. Қазақстан Республикасының экологиялық заңнамасын саралау. (Journal of actual problems of jurisprudence, 2016)
This article reveals the analysis of the legislation of the Republic of Kazakhstan relating to ecological responsibility of nature users. Such terms as “the system of assessment of the impact on the environment”, “environmental damage”,“direct” and “indirect” methods of economic assessment of damage are analyzed in the article. On the basis of foreign experience research the author offers the ways of improvement of national ecological legislation.Мақала Қазақстан Республикасының табиғат пайдаланушылардың экологиялық жауапкершілігі мәселесі бойынша заңнаманы талдауға арналған. Мақалада «қоршаған ортаға ықпал жасау бағалау жүйесі», «қоршаған ортаға зиян», залалды экономикалық бағалаудың «тура» және «жанама» әдістерi сияқты ұғымдар талданады.Мақала авторы шетел тәжірибесін зерттеп ұлттық экологиялық заңнаманың жетілдіру жолдарын ұсынады.
Keywords: ecological legislation; ecological responsibility; nature users; society ecologization; deglaciation; economic assessment of environmental damage; “green economy”; national fund for the protection and recovering of the environment; экологиялық заңнама